Financial comparisons of under‐vine management systems in four South Australian vineyard districts*. (20th December 2020) - Nordblom, Thomas; Penfold, Chris; Whitelaw‐Weckert, Melanie; Norton, Mark; Howie, Jake; Hutchings, Timothy
Abstract : Conventional viticultural practice in Australia and elsewhere involves removal of under‐vine vegetation using herbicides or cultivation. Concerns over the long‐term effects of herbicides on soil health, evolution of resistant weeds and possible impacts on human health motivate the search for alternative weed management options. Industry‐supported trials on commercial vineyards in four South Australian regions investigated standard practices of straw mulch and bare earth created with herbicides, compared to under‐vine cover crops, focusing on soil health attributes (soil carbon, soil microbiological processes, etc.) and grape yields in 2016 and 2017. Measured yields with the Control (herbicide) treatment were combined with published district grape prices and yields over the 12‐year (2006–2017) period, defining multivariate distributions of gross revenues ($/ha). Assuming all treatments produce grapes of equal quality and price as the Control, our results showed median per‐hectare gross margins greater than the Control in the Barossa district, lower than Control in Riverland, and mixed results in Langhorne Creek and Eden Valley. Multi‐year risk profiles, based on decadal whole‐farm (50 ha) cash flows for each treatment, were calculated using Monte Carlo analysis, based on historical yield and price distributions. These risk profiles showed the under‐vine treatments may result in major differences in long‐term vineyard financial viability.